Terapi Tawa Terhadap Tingkat Tekanan Darah Pada Penderita Hipertensi - yati, indri (Sahabat Publikasi Kuu, 2024)
Introduction: Hypertension is a disease that can be treated with pharmacological and non-pharmacological therapies. One of the non-pharmacological treatments for hypertension is laughter therapy. Laughter is a mental or emotional expression shown through facial expressions and certain sounds. Purpose: This study aims to determine whether laughter therapy affects blood pressure levels in patients with hypertension. Method: This study is a quantitative study with a pre-experimental research design with (one group pretest-posttest design). The number of samples was 68 people. The instrument is a checklist with a digital sphygmomanometer tool brand Omron Tensimeter Automatic Blood Pressure Monitor series HEM-7121 and laughter therapy SOP. Normality test, using the Kolmogorov Smirnov test. Analysis of pre and post test blood pressure data using the Wilcoxon test. Result: The decrease in respondents' blood pressure was confirmed by the results of the Wilcoxon statistical test on systolic and diastolic blood pressure obtained a p-value = 0.001, so it was concluded that there was an effect of laughter therapy on changes in blood pressure in elderly people with hypertension in the elderly posyandu. Conclution: Blood pressure before giving laughter therapy was 160/90 mmHg and after laughter therapy became 150/70 mm/Hg so that there was a decrease in blood pressure. Laughter therapy can be said to be effective for lowering blood pressure, a relaxation method that is thought to reduce blood pressure in people with hypertension.